Book review of The future of ISIS: Regional and international politics by Feisal al-Istrabadi and Sumit Ganguly - Hossain, Ishtiaq (The Islamic Foundation, London, the UK, 2020)
On March 22, 2014, the White House issued an official statement announcing the military defeat of the Islamic State of Iraq and Syria (ISIS), a Salafi Jihadist group. Five years later, on October 27, 2019, President Donald Trump announced the killing of Abu Bakr al-Baghdadi, the self-styled amir al-mu’minin of ISIS in a military operation by US Special Forces. The destruction of ISIS military forces in Syria and Iraq marked the defeat of the Caliphate, which was proclaimed by Abu Bakr al-Baghdadi on June 29, 2014. However, the military defeat of ISIS and the killing of its leader did not signal the end of ISIS as a threat to the world.